Gendering conflict and violence in Zimbabwe, 1960-2013: the case of Bulawayo Metropolitan Province - King, Monica Dorothy (Midlands State University, 2022)
The problem of political violence permeated the landscape of Zimbabwe, during both the colonial and post-colonial periods. The questions tackled were: are perpetrators of violence men or women or both? Do the victims of political violence constitute of men or women? To what extent are women as compared to men perpetrators of violence? In what forms and contexts has the problem manifested itself? What are the mechanisms that have been used to resolve conflicts? By focusing on Bulawayo Metropolitan Province, the thesis examined the political violence which was perpetrated during the period 1960-2013. The study argued that in Zimbabwe from the colonial to the post-colonial era, political conflicts involved both men and women differently. It interrogated the contention that in conflict situations men are the perpetrators while women are weak and vulnerable to victimhood. An examination of different cases of violence that transpired in the racist context of colonial Zimbabwe and in the black dominated post-colonial era revealed that both men and women can be perpetrators or victims, depending on the typology of violence prevailing. Using the case of Bulawayo, incidences of colonial racialized political violence as well as post-colonial incidences of political violence, the study established the differential experience and participation in violence by women compared to men. It established that the story of gendered participation in different typologies of political violence defies the simplistic categorisation of men as perpetrators and women as victims. The narrative is more nuanced given that men show a preponderance as both perpetrators and victims in some cases more than women while in other cases women are active agents who equally perpetrate violence in so much as they are victims in other cases. For instance, in protests against the 1961 Constitution, women in Bulawayo instigated political violence by demonstrating outside the Magistrate Court, thereby prompting the colonial state to arrest 75 of them. The violence of the Second Chimurenga involved both men and women as they fought against colonial oppression. During the post-colonial era both men and women were victims of violence- notable episodes of such violence were the ‘Gukurahundi’ of the 1980s and Operation Murambatsvina of 2005. To problematize the phenomenon of political violence, the thesis used Slavoj Zizek’s ideas on violence as well as Max Weber’s Conflict Theory. In analysing the conflict resolution mechanisms, the thesis used Galtungs’s ideas of positive and negative peace. The study revealed that the agreements to end political conflicts in Zimbabwe deployed negative peace methodologies. Furthermore, the thesis concludes that to solve political conflicts in Zimbabwe one needs to use conflict resolution mechanisms that uproot the causes of the conflicts.